Overview of Knowledge and Attitude of Adolescents Towards Free Sex in the Pannampu District, Makassar City - Nurhayati, Nurhayati (Hasanuddin Medan, 2022)
Problems that are often experienced by teenagers today are issues surrounding sexuality, especially premarital sex or free sex. Data from the World Health Organization (WHO), which conducted research in several developing countries, shows that around 40% of young men and young women aged 18 years have had sex even without being married. Based on research in various big cities in Indonesia, around 20 to 30% of teenagers admit to having had sex. The aim of the research was to determine the description of teenagers' knowledge and attitudes towards free sex in Pannampu Village, Makassar City. The type of research is descriptive observational. The sample in the research was 98 teenagers aged 13-18 years in Pannampu Village, Makassar City, using proportional random sampling techniques. The results showed that based on knowledge, the majority of respondents had less knowledge about free sex, namely 58 people (59.2%), while based on attitude, the majority of respondents had a positive attitude towards free sex behavior, namely 66 people (67.3% ). Based on the results of the research, it was concluded that knowledge can influence teenagers' attitudes towards engaging in free sex. The better teenagers' knowledge about free sex, the better their attitudes and behavior will be in avoiding free sexual behavior. It is recommended that health workers provide education about the dangers of free sex to teenagers to increase teenagers' knowledge about the impacts that can be caused by free sex.